Acceleration of chondrogenic differentiation of human mesenchymal stem cells by sustained growth factor release in 3D graphene oxide incorporated hydrogels. (15th March 2020) - Shen, He; Lin, Hang; Sun, Aaron X.; Song, Saijie; Wang, Bing; Yang, Yuanheng; Dai, Jianwu; Tuan, Rocky S.
ABSTRACT: Damaged articular cartilage has limited self-healing capabilities, leading to degeneration that affects millions of people. Although cartilage tissue engineering is considered a promising approach for treatment, robust and long-term chondrogenesis within a 3-dimensional (3D) scaffold remains a major challenge for complete regeneration. Most current approaches involve incorporation of transforming growth factor-β (TGF-β) into the scaffold, but have limited utility owing to the short functional half-life and/or rapid clearance of TGF-β. In this study, we have tested the incorporation of graphene oxide nanosheets (GO) within a photopolymerizable poly-D, l -lactic acid/polyethylene glycol (PDLLA) hydrogel, for its applicability in sustained release of the chondroinductive growth factor TGF-β3. We found that with GO incorporation, the hydrogel scaffold (GO/PDLLA) exhibited enhanced initial mechanical strength, i.e., increased compressive modulus, and supported long-term, sustained release of TGF-β3 for up to 4 weeks. In addition, human bone marrow-derived mesenchymal stem cells (hBMSCs) seeded within TGF-β3 loaded GO/PDLLA hydrogels displayed high cell viability and improved chondrogenesis in a TGF-β3 concentration-dependent manner. hBMSCs cultured in GO/PDLLA also demonstrated significantly higher chondrogenic gene expression, including aggrecan, collagen type II and SOX9, and cartilage matrix production when compared to cultures maintained in GO-free scaffolds containing equivalent amounts of TGF-β3. Upon subcutaneous implantation in vivo, hBMSC-seeded TGF-β3-GO/PDLLA hydrogel constructs displayed considerably greater cartilage matrix than their TGF-β3/PDLLA counterparts without GO. Taken together, these findings support the potential application of GO in optimizing TGF-β3 induced hBMSC chondrogenesis for cartilage tissue engineering. Statement of Significance: In this work, we have developed a graphene oxide (GO) incorporated, photocrosslinked PDLLA hybrid hydrogel for localized delivery and sustained release of loaded TGF-β3 to seeded cells. The incorporation of GO in PDLLA hydrogel suppressed the burst release of TGF-β3, and significantly prolonged the retention time of the TGF-β3 initially loaded in the hydrogel. Additionally, the GO improved the initial compressive strength of the hydrogel. Both in vitro analyses and in vivo implantation results showed that the GO/PDLLA constructs seeded with human mesenchymal stem cells (hMSCs) showed significantly higher cartilage formation, compared to GO-free scaffolds containing equivalent amount of TGF-β3. Findings from this work suggest the potential application of the GO-TGF/PDLLA hydrogel as a functional scaffold for hMSC-based cartilage tissue engineering. Graphical abstract: Image, graphical abstract